2021
DOI: 10.1002/rrq.414
|View full text |Cite
|
Sign up to set email alerts
|

Monolingual and Bilingual Reading Processes in Russian: An Exploratory Scanpath Analysis

Abstract: In the present study, we used a scanpath approach to investigate reading processes and factors that can shape them in monolingual Russian‐speaking adults, 8‐year‐old children, and bilingual Russian‐speaking readers. We found that monolingual adults’ eye movement patterns exhibited a fluent scanpath reading process, representing effortless processing of the written material: They read straight from left to right at a fast pace, skipped words, and regressed rarely. Both high‐proficiency heritage‐language speaker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…The relationship between scanpath regularity measures and comprehension is mostly consistent with previous studies suggesting that more regular scanpaths tend to be associated with better comprehension and reading skills (Parshina et al, 2021;von der Malsburg et al, 2015). This pattern was found across comprehension measures, suggesting the existence of a single optimal reading process, and that readers who deviate from it in some way tend to have lower comprehension scores.…”
Section: Regular Scanpaths As Indicative Of Good Reading Comprehensionsupporting
confidence: 88%
See 2 more Smart Citations
“…The relationship between scanpath regularity measures and comprehension is mostly consistent with previous studies suggesting that more regular scanpaths tend to be associated with better comprehension and reading skills (Parshina et al, 2021;von der Malsburg et al, 2015). This pattern was found across comprehension measures, suggesting the existence of a single optimal reading process, and that readers who deviate from it in some way tend to have lower comprehension scores.…”
Section: Regular Scanpaths As Indicative Of Good Reading Comprehensionsupporting
confidence: 88%
“…A potential limitation to predictive power of scanpath regularity is the aforementioned fact that readers adapt their reading strategies to differences in task demands between reading tasks (Bax & Chan, 2019;Kaakinen & Hyönä, 2010;O'Reilly et al, 2012;Radach et al, 2008;Schotter, Bicknell, et al, 2014). Like all eye-movement measures, this will limit the degree to which scanpath regularity identified in previous studies (e.g., the 'fluent' strategy in Parshina et al, 2021) can generalize across reading tasks and studies. However, unlike other eye-movement measures, scanpath regularity assesses eye movements relative to the most common reading strategy employed to meet task demands -regardless of what those demands are.…”
Section: Scanpaths As a Measure Of Eye-movement Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…As such, scanpaths capture the overall pattern of gaze behavior during reading and can be used to investigate global reading strategies of sentences or whole passages of text. Critically, scanpaths have been shown to capture effects that are not necessarily caught by word-level measures (Mézière et al, 2022;Parshina et al, 2022;Von der Malsburg & Vasishth, 2011, 2013. In an early study, von der Malsburg and Vasishth (2013) used scanpaths to identify the processing strategies of readers when they encounter garden path sentences and considered the mediating effect of WMC on which strategy readers used.…”
Section: Scanpath Analyses Of Eye Movement Datamentioning
confidence: 99%
“…Critically, these distinct patterns and strategies could not have been identified with standardly used word-level measures, showing that scanpaths can capture features of eye-movement behavior not caught by word-level measures. In addition, they found that readers' re-reading behavior and the extent to which they use those three strategies interacted with their WMC, showing that scanpaths are also useful to investigate the role of individual differences in processing strategies used during reading (see also Mézière et al, 2022;Parshina et al, 2022). Hence, scanpaths provide an ideal tool to investigate the strategies readers use in the processing written irony, as well as the role of individual differences such as WMC or comprehension accuracy in reading literal and ironic passages of text.…”
Section: Scanpath Analyses Of Eye Movement Datamentioning
confidence: 99%